Fantastic beasts and where to find them - Rowling, J. K. (New York : Arthur A. Levine Books, 2001)
A textbook used by apprentice wizard Harry Potter in his studies at Hogwarts School of Witchcraft and Wizardry, providing descriptions of a wide variety of magical creatures, and offering advice on their care. Proceeds from this book will go to Comic Relief U.K.
"Comic Relief"--Cover p. [4].
"Obscurus Books, 18a Diagon Alley, London.".
"Property of Harry Potter"--Cover.
Cover title: Fantastic beasts & where to find them.
Written by J.K. Rowling as a fictitious author.
Book Report.
Keywords: Animals, Mythical -- Fiction; Fantasy; Monsters -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Monsters -- Fiction; Mythical animals -- Fiction; Potter, Harry (Fictional character) -- Fiction; Fantastic fiction